1993
DOI: 10.4319/lo.1993.38.7.1365
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of kinetic growth of Chlorella vulgaris cells by the method of integral and dynamic light scattering

Abstract: Laboratory measurements of light scattering on axenic cultures of the unicellular alga Chlorella vulgaris confirm multilevel light scattering by the cell (i.e. both by the outer cell membrane and the internal structure of the cell, as well as by its molecular structure). The technique of dynamic light scattering and analysis by the regulation method suggest that the light scattering phenomena is affected by particles of sizes corresponding either to the overall dimensions of the cell or to the dimensions of it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Compared to the volume scattering function, Müller matrix of microalgae suspension contains more detailed information on the inner structure, size and shape of the cells (Quinby-Hunt et al 1989;Witkowski et al 1998;Witkowski et al 1993;Volten et al 1998). It has been shown that the elements M34, and M11 are sensitive to the size of the algae (Quinby-Hunt et al 1989), the difference M22-M11 to the shape (Quinby-Hunt et al 1989), and the elements M11, M12, M34 to the inner cellular structure (Quinby-Hunt et al 1989;Witkowski et al 1993;Volten et al 1998). In addition, Witkowski et al (Witkowski et al 1998) measured all elements of the Müller matrix and observed optical activity (or rotation of linearly polarized light) indicated by non-zero readings for M13, M14 and M24.…”
Section: Optics Of Cell Suspensionsmentioning
confidence: 99%
“…Compared to the volume scattering function, Müller matrix of microalgae suspension contains more detailed information on the inner structure, size and shape of the cells (Quinby-Hunt et al 1989;Witkowski et al 1998;Witkowski et al 1993;Volten et al 1998). It has been shown that the elements M34, and M11 are sensitive to the size of the algae (Quinby-Hunt et al 1989), the difference M22-M11 to the shape (Quinby-Hunt et al 1989), and the elements M11, M12, M34 to the inner cellular structure (Quinby-Hunt et al 1989;Witkowski et al 1993;Volten et al 1998). In addition, Witkowski et al (Witkowski et al 1998) measured all elements of the Müller matrix and observed optical activity (or rotation of linearly polarized light) indicated by non-zero readings for M13, M14 and M24.…”
Section: Optics Of Cell Suspensionsmentioning
confidence: 99%
“…The chloroplast of an autotrophic eukaryotic cell is the membrane bound organelle containing the highly absorbing pigment-protein complexes responsible for light harvesting and photosynthesis, and it will exert a profound optical effect. Algal related studies investigating the effects of cellular internal structure on scattering (Witkowski et al, 1993(Witkowski et al, , 1998 and absorption packaging (Geider and Osborne, 1987) indicate the importance of chloroplasts in modifying both the absorbing and scattering properties of algal cells. Imposing a simple two-layered geometry upon a hypothetical algal cell thus requires some knowledge of the variability of chloroplast size, or more appropriately, the relative chloroplast volume.…”
Section: Chloroplast Morphometricsmentioning
confidence: 99%
“…The angular pattern of light scattering can also contain useful information about the composition of particulate assemblages, including the bulk refractive index of particles [15][16][17][18][19]. In addition, measurements of the scattering matrix that provide information about polarization effects of light scattering [15,[20][21][22][23] have the potential for identifying and discriminating different types of particles, such as phytoplankton species or minerals, which are present in complex natural assemblages [24][25][26][27][28][29][30][31][32][33][34]. Despite the potential usefulness of information provided by light scattering measurements, the complexity and variability in composition of natural particulate assemblages impose significant challenges in achieving an understanding of bulk light-scattering properties of seawater in terms of detailed compositional characteristics of particulate matter [35].…”
Section: Introductionmentioning
confidence: 99%